In Vitro Dermo-Cosmetic Evaluation of Bark Extracts from Common Temperate Trees - Hubert, Jane; Angelis, Apostolis; Aligiannis, Nektarios; Rosalia, Michalea; Abedini, Amin; Bakiri, Ali; Reynaud, Romain; Nuzillard, Jean-Marc; Gangloff, Sophie C.; Skaltsounis, Alexios-Leandros; Renault, Jean-Hugues (Planta Medica, 2016)
Wood residues produced from forestry activities represent an interesting source of biologically active, high value-added secondary metabolites. In this study, 30 extracts from 10 barks of deciduous and coniferous tree species were investigated for their potential dermo-cosmetic use. The extracts were obtained from Fagus sylvatica, Quercus robur, Alnus glutinosa, Prunus avium, Acer pseudoplatanus, Fraxinus excelsior, Populus robusta, Larix decidua, Picea abies, and Populus tremula after three successive solid/liquid extractions of the barks with n-heptane, methanol, and methanol/water. All extracts were evaluated for their radical scavenging capacity, for their elastase, collagenase, and tyrosinase inhibitory activities, as well as for their antibacterial activity against gram-positive Staphylococcus aureus. In parallel, the global metabolite profiles of all extracts were established by 1D and 2D NMR and related to their biological activity. The results showed that the methanol extracts of Q. robur, A. glutinosa, L. decidua, and P. abies barks exhibit particularly high activities on most bioassays, suggesting their promising use as active ingredients in the dermo-cosmetic industry.
Keywords: barks; natural products; dermo-cosmetics; DPPH; Collagenase; elastas; tyrosinase; Staphylococcus aureus; nuclear magnetic resonance spectroscopy